1992
DOI: 10.1172/jci116095
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic uptake of a modified low molecular weight heparin in rats.

Abstract: Fractionated and unfractionated heparins are widely used as antithrombotic agents. Because of their heterogeneous composition, it is difficult to study the pharmacokinetics of these drugs. We now report on a new method for labeling low molecular weight heparins with "31I by binding tyramine to the anhydromannose end of the molecules. We examined the pharmacokinetics of the compound by intravenous injection of '31I-tyramine-heparin into Wistar rats. About 18% of the activity was found in the liver, whereas 33% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This was true for low molecular weight heparin, which is taken up by a scavenger receptor in the liver. 38) HA showed high liver distribution and cleared the circulatory system very rapidly, confirming previous findings that HA is rapidly absorbed by liver endothelial cells via receptor-mediated endocytosis.…”
Section: Discussionsupporting
confidence: 89%
“…This was true for low molecular weight heparin, which is taken up by a scavenger receptor in the liver. 38) HA showed high liver distribution and cleared the circulatory system very rapidly, confirming previous findings that HA is rapidly absorbed by liver endothelial cells via receptor-mediated endocytosis.…”
Section: Discussionsupporting
confidence: 89%
“…Neither poly(A) nor heparin is a broad-spectrum SR inhibitor. Nonetheless, both poly(A) and heparin have previously been shown to inhibit the uptake of a select subset of SR ligands by macrophages both in vitro and in vivo (15,53,58,65). Of note is that the experiment shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…We found that poly(A) and heparin caused a partial reduction of Ad uptake by KCs, although this was statistically significant only for poly(A). Both poly(A) and heparin are known to inhibit the clearance of distinct subsets of SR ligands, apparently by binding to only a subset of SRs (15,53,58,65). Since a reduction in the amount of Ad taken up by KCs should increase the availability of Ad to other tissues, we also tested selected SR ligands for their ability to enhance Ad transduction of hepatocytes in vivo.…”
Section: Vol 82 2008 Mechanisms For Uptake Of Adenovirus By Kupffermentioning
confidence: 99%
“…Most previous studies have used iodinated (3,65) or tritiumlabeled heparin (11,73,77) for metabolic studies of heparin and assessment of organ distribution by autoradiography and recovered radioactivity in isolated organs. However, FITClabeled UFH has also been shown to be suitable for studying heparin distribution and metabolism (11).…”
Section: Discussionmentioning
confidence: 99%